Faktor Lingkungan Sekolah Atas Motivasi Belajar dan Sel-Regulation Siswa di SMA IT Daarul Rahman - Okta Rosfiani; M. Abdul Halim; Khamdi Iskandar; M. Ardiansyah; Husni Mubarok (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The influence of school environment factors on students learning motivation andself-regulation at SMA IT. The research focuses on identifying aspects of theschool environment such as teacher support, peer interactions, facilities, andschool culture that either enhance or hinder students intrinsic motivation and theirability to self-regulate learning. Data were collected through in-depth interviews,observations, and document analysis involving students, teachers, and schooladministrators. The findings reveal that a positive school environment,characterized by collaborative learning spaces, supportive teacher-studentrelationships, and structured academic policies, significantly boosts studentsmotivation and self-regulation. Conversely, inadequate facilities or unsupportivesocial dynamics may negatively impact these outcomes. The study highlights theneed for schools to cultivate an environment that fosters autonomy, competence,and relatedness to optimize student engagement and self-regulated learning.Keywords: school environment, learning motivation, self-regulation.